Holographic detection of nonradiative transitions in oxygen molecules: digital and classical approach. (November 2015) - Beltukova, D M; Belashov, A V; Petrov, N V; Semenova, I V; Vasyutinskii, O S
Abstract: The paper presents a novel approach to detect and monitor nonradiative transitions in singlet oxygen molecules in water by means of holographic recording of thermal disturbances. The approach is realized experimentally using classical and digital holographic techniques. Advantages and disadvantages of each of the techniques are considered.